2-Aminophenanthroline dimer stabilized the C–C mismatched duplex DNA. Issue 4 (15th February 2015) - Li, Jinxing; Matsumoto, Jun; Otabe, Takahiro; Dohno, Chikara; Nakatani, Kazuhiko
Graphical abstract: Abstract: New ligands with three-ring system for the recognition of a cytosine bulge and a cytosine–cytosine mismatch were designed and synthesized. The 2-amino-1, 10-phenanthroline was selected as a recognition unit among the possible three-ring systems of a parent recognition unit of 2-amino-1, 8-naphthyridine. The 3-aminopropanamide of 2-amino-1, 10-phenanthroline (APM ) bound to the cytosine bulge DNA. Other single nucleotide bulges were stabilized by the ligand with much lower efficiency. The dimer APD consisting of two molecules of APM was found to stabilize the C–C mismatch DNA selectively. Structure–activity relationship studies revealed that the APD -binding to the C–C mismatch DNA required both phenanthroline heterocycles in a molecule.